THE JUDGE'S CONSIDERATION OF THE CHILD AS THE PERPETRATOR OF SEXUAL VIOLENCE THAT RESULTED IN THE VICTIM'S DEATH: AN ANALYSIS OF DECISION NUMBER 50/PID. SUS-ANAK/2024/PN PLG & 51/PID. SUS-ANAK/2024/PN PLG - Setiawan, Muhammad Bukhori (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article seeks to achieve two objectives: first, to analyze the various legal frameworks that govern the treatment of children in such cases, and second, to identify the factors that the court considers when deciding a child offender to be guilty of sexual violence resulting in death. This research focuses on two court decisions: Decision Number 50/Pid.Sus-Anak/2024/PN Plg and Decision Number 51/Pid.Sus-Anak/2024/PN Plg. The research approach used is normative juridical, and involves an analytical descriptive methodology. Judges considered the age, role, and opinions of community counselors when making decisions about ABH cases, according to the study. The principles of restorative justice and the best interests of children as outlined in the Law on the Juvenile Criminal Justice System are the basis of the decision.